Macrophages in the Human Cochlea: Saviors or Predators—A Study Using Super-Resolution Immunohistochemistry - Liu, Wei; Molnar, Matyas; Garnham, Carolyn; Benav, Heval; Rask-Andersen, Helge (Frontiers in Immunology, 2018)
The human inner ear, which is segregated by a blood/labyrinth barrier, contains resident macrophages (CD163, IBA1-, and CD68-positive cells) within the connective tissue, neurons and supporting cells. In the lateral wall of the cochlea, these cells frequently lie close to blood vessels as perivascular macrophages. Macrophages are also shown to be recruited from blood-borne monocytes to damaged and dying hair cells induced by noise, ototoxic drugs, aging and diphtheria toxin-induced hair cell degeneration. Precise monitoring may be crucial to avoid self-targeting. Macrophage biology has recently shown that populations of resident tissue macrophages may be fundamentally different from circulating macrophages. We removed uniquely preserved human cochleae during surgery for treating petro-clival meningioma compressing the brain stem, after ethical consent. Molecular and cellular characterization using antibodies against IBA1, TUJ1, CX3CL1 and type IV collagen, and super-resolution structured illumination microscopy (SR-SIM) were made together with transmission electron microscopy. High resolution microscopy disclosed remarkable phenotypic variants of IBA1 cells closely associated with the spiral ganglion cells. Monitoring cells adhered to neurons with “synapse-like” specializations and protrusions. Active macrophages migrated occasionally nearby damaged hair cells. Results suggest that the human auditory nerve is under the surveillance and possible neurotrophic stimulation of a well-developed resident macrophage system. It may be alleviated by the non-myelinated nerve soma partly explaining why, in contrary to most mammals, the human’s auditory nerve is conserved following deafferentiation. It makes cochlear implantation possible, for the advantage of the profoundly deaf. The IBA1 cells may serve additional purposes such as immune modulation, waste disposal and nerve regeneration. Their role in future stem cell-based therapy needs further exploration.